021 The effectiveness of dexmedetomidine for paediatric sedation in a radiology setting. (December 2018) - Cerullo, A; Stuart, C
Abstract : Background: Paediatric patients presenting for MRI scans may not always be able to lie still. In the past, the options for these children were to either administer a Chloral Hydrate sedation or a General Anaesthetic, both of which have their limitations. Nurse-led Chloral Hydrate sedation has limitations including only being able to sedate children less than 20kgs with no underlying respiratory issues, and general anaesthetic has both safety and resource limitations. This led us to investigate the use of dexmedetomidine as a protocol for nurse-led sedation in the MRI setting at GOSH. Aims: To examine whether dexmedetomidine would be a useful medication for the use of obtaining paediatric MRI scans, and prevent children from having unnecessary general anaesthetics. The main areas of focus were patient safety, patient (and their families) experience, and the effect on the number of general anaesthetics undertaken. Method: Quantitative data was taken from audit sheets, with graphing techniques used to determine the safety of pharmacodynamics. The RIS database was also interrogated, with comparative exercises undertaken to determine the usage of lists. Qualitative data was collected through 'friends and family' tests, to evaluate patient/parent experience, and to compare experiences between sedation and general anaesthetic for those patients who experienced both. Results: The use of dexmedetomidine showed no unplanned admissions and no adverse events other than vomiting. General anaesthetic lists had to be converted into sedation lists due to demand. Furthermore, results from the 'friends and family' test suggested parents would prefer future scans under sedation rather than general anaesthetic. Conclusion: The study showed dexmedetomidine worked well as a sedative for paediatric MRI scans. The protocol is still evolving and further improvements are being investigated, but on the whole the study suggested its use was both effective, and a positive change for patient experience.